DETERMINANTS OF ORGANIC FOOD CONSUMPTION OF CONSUMERS IN BANGALORE CITY- A STUDY (International Journal of Food and Nutritional Sciences, 2022)
India has emerged as one of the largest markets in the world for organic food. The organic foods products are healthy, without chemicals or preservatives, are completely natural and are much better than conventional foods in terms of the various benefits that they provide to one and all. The health of citizens is a core concern for every nation. The objective of this work was to investigate thedeterminants of organic food consumption of consumers in Bangalore city. Convenient sampling technique was adopted for the study purpose. Bangalore city was chosen as major study area. The list of organic retail stores in the city was obtained and 56 stores were randomly chosen. A sample size of 788 was formed by conveniently selecting on an average of 25 customers from each store they visited. Primary information pertaining to their perception, preferences and buying motives for various organic food products were obtained. Statistical Package for Social Science (SPSS.13) trial version was used to analyse the data. Multiple regression analysis was used as the main statistical tool to find out the significant influence of factors determining organic food consumption of consumers in Bangalore city. The findings highlight the The unique contribution for the variables of informational factors and the variables of consumer’s psychographic factors have the significant influence on consumption of organic food products by the consumers in Bangalore city.